SISTEM PERLINDUNGAN SOSIAL JEPANG: MENUJU NEGARA WELFARE PLURALISM - Nuryana, Mu’man (Sosio Informa, 2006)
(Social ProtectionSystem in Jepang for Welfare Pluralism Country) - This article attempts to describe social security system in Japan, with special emphasize on its objectives, purposes and functions. However, Japanese social security systems will be looked at the present situation in order to know how they have been established. Indeed, social security system in Japan is a general expression that includes the systems in the following fields: social insurance systems including medical and pension insurance programs, public assistance systems to ensure the minimum level of sound and cultural living, social welfare systems for children, mothers and children, people of disabilities and for the elderly, medical care systems, and the systems for public and environmental health. And there are objectives and functions for each social security system in. A recognition into the objectives and functions of social security systems in Japan will help us in analyzing the present situation of, evaluating, or examining the desirable future of social security in Indonesia.